Papain production - Boquiren, Randifer E. (College of Engineering, 1999)
Product: Papain powder and suspension -- Plant Capacity: 5,600 kg/year -- Selling price: Powder - 3,300Php/kg, Suspension: 1,200 Php/kg -- Total capital investment: Php 16,330,299.00 -- Total production cost: Php 12,338,364.00 -- Return on investment: 22.74% -- Payback period: 2.60 years -- Location: Cavite Export Processing Zone, Rosario, Cavite